2018
DOI: 10.1039/c8cc04543g
|View full text |Cite
|
Sign up to set email alerts
|

Convenient synthesis of selenyl-indoles via iodide ion-catalyzed electrochemical C–H selenation

Abstract: Reported herein is a transition metal- and oxidant-free method for the synthesis of selenyl heteroarenes with diselenides through iodide ion-catalyzed electrolytic selenation. This direct C(sp2)-H selenation strategy, with reduced environmental impact, provides efficient access to a host of selenyl indoles and some other N-heteroarenes under aerobic and galvanostatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 36 publications
2
45
0
Order By: Relevance
“…In the presence of I 2 , through anodic oxidation, the intermediate 43 is formed. On the other hand, in pathway B the intermediate 3-iodo-indole 44 is formed, similar to the mechanism proposed by Sun and co-workers (Scheme 2), [61] as previously described. After the addition of iodine, the cationic intermediate 45 reacts with sodium benzenesulfinate generating the intermediate 46.…”
Section: Electrochemical C(sp 2 )à H Chalcogenationsupporting
confidence: 84%
“…In the presence of I 2 , through anodic oxidation, the intermediate 43 is formed. On the other hand, in pathway B the intermediate 3-iodo-indole 44 is formed, similar to the mechanism proposed by Sun and co-workers (Scheme 2), [61] as previously described. After the addition of iodine, the cationic intermediate 45 reacts with sodium benzenesulfinate generating the intermediate 46.…”
Section: Electrochemical C(sp 2 )à H Chalcogenationsupporting
confidence: 84%
“…The curves of NH 4 I with 1 a (curve e) and NH 4 I with 2 a (curve f) were also measured, respectively, as shown in Figure 2, and there was no change, which indicated that I À did not oxidize the substrates in this reaction. [31] At the cathode, The COMMUNICATIONS asc.wiley-vch.de I 2 and proton are reduced to the iodine anion and hydrogen, which completes the rection cycle. At the anode, the electrochemical oxidation of I À initially results in the formation of I + by losing two electrons, which then react with olefinic alcohols to provide the iodonium cations intermediate A.…”
Section: Scheme 1 Synthesis Of O-containing Heterocyclesmentioning
confidence: 99%
“…Finally, the target product 3 and a half molar equivalent of I 2 are obtained by a rapid chemical selenation. [31] At the cathode, The COMMUNICATIONS asc.wiley-vch.de I 2 and proton are reduced to the iodine anion and hydrogen, which completes the rection cycle.…”
Section: Communications Ascwiley-vchdementioning
confidence: 99%
“…Jiang, Sun and their co‐workers disclosed a transition metal‐ and oxidant‐free method for the synthesis of selenyl heteroarenes 90 with diselenides in which KI was used both as the electrolyte and the catalyst (Scheme ) . Two possible reaction pathways are potentially operative.…”
Section: Electrochemical Functionalization Of Indole Derivativesmentioning
confidence: 99%